Factors affecting in-service teachers’ informatization instructional leadership in China - Wei Lili; Yoon Fah Lay (International Journal of Education and Practice, 2024)
The ubiquity of instructional leadership integrated with technology has necessitated research into the application of instructional leadership and its influencing factors. The aim of this study is to investigate contributing factors to in-service teachers’ informatization instructional leadership by determining the relationship between use expectancy, social influence, facilitating conditions, computer self-efficacy, blended teaching competence, behavioral intention and teachers’ informatization instructional leadership. Quantitative research is employed using a questionnaire to collect data. The sample comprises 230 randomly selected in-service teachers from private undergraduate universities in Xi’an City, Shaanxi Province, China. Data analysis was carried out using SmartPLS. The results show that use expectancy, facilitating conditions, computer self-efficacy, blended teaching competence and behavioral intention all have a positive and significant effect on teachers’ informatization instructional leadership. Use expectancy, computer self-efficacy and blended teaching competence have a positive and significant effect on behavioral intention, and behavioral intention significantly mediates the relationships between use expectancy, computer self-efficacy, blended teaching competence and teachers’ informatization instructional leadership. The research provides practical guidance for universities attempting to implement or improve teachers’ informatization instructional leadership practices. Efforts for policymakers to develop teachers’ informatization instructional leadership should consider the importance of not only use expectancy and facilitating conditions but also computer self-efficacy, blended teaching competence, and the role of behavioral intention to use teachers’ informatization instructional leadership.